Dairy products and the Maillard reaction: A promising future for extensive food characterization by integrated proteomics studies. (15th March 2017) - Arena, Simona; Renzone, Giovanni; D'Ambrosio, Chiara; Salzano, Anna Maria; Scaloni, Andrea
Highlights: The Maillard reaction affects milk proteins by introducing a number of chemical modifications. Dozens of early, intermediate and advanced glycation end-products have been characterized. Proteomics has been recently used to assign modification protein targets and modified residues. Gel-based and shotgun milk proteomic applications are here reviewed according to a Maillard-oriented perspective. Abstract: Heating of milk and dairy products is done using various technological processes with the aim of preserving microbiological safety and extending shelf-life. These treatments result in chemical modifications in milk proteins, mainly generated as a result of the Maillard reaction. Recently, different bottom-up proteomic methods have been applied to characterize the nature of these structural changes and the modified amino acids in model protein systems and/or isolated components from thermally-treated milk samples. On the other hand, different gel-based and shotgun proteomic methods have been utilized to assign glycation, oxidation and glycoxidation protein targets in diverse heated milks. These data are essential to rationalize eventual, different nutritional, antimicrobial, cell stimulative and antigenic properties of milk products, because humans ingest large quantities of corresponding thermally modified proteins on a daily basis and these molecules also occur in pharmaceuticals and cosmetics. This review provides an updated picture of the procedures developed for the proteomic characterization of variably-heated milk products, highlighting their limits as result of concomitant factors, such as the multiplicity and the different concentration of the compounds to be detected.